A facile and chemoselective synthesis of 1, 4-benzodiazepin-2-ones and dienyl thiazolidin-4-ones. Issue 62 (15th June 2016) - Kuila, Bilash; Kumar, Yogesh; Mahajan, Dinesh; Kumar, Kapil; Singh, Prabhpreet; Bhargava, Gaurav
Abstract : A chemoselective synthesis of novel 1, 4-benzodiazepin-2-ones and dienyl thiazolidin-4-one carboxylates in excellent yields by ring transformation reactions of functionally decorated 2-azetidin-3-thiazolidin-4-ones is reported. Abstract : An efficient protocol for chemoselective synthesis of previously unknown 1, 4-benzodiazepin-2-ones and dienyl thiazolidin-4-one carboxylates in excellent yields by ring transformation reactions of functionally decorated 2-azetidin-3-thiazolidin-4-ones is reported.